The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/su14042455
|View full text |Cite
|
Sign up to set email alerts
|

Global Challenges and Responses: Agriculture, Economic Globalization, and Environmental Sustainability in Central Asia

Abstract: Economic globalization (EG) accelerates very fast in Central Asia. This could cause environmental degradation, according to the environmental Kuznets curve (EKC) hypothesis. The study aims to determine how the EG of agriculture impacts environmental sustainability, and to test the EKC hypothesis on the agricultural sector in six Central Asian countries. Particularly, some main hypotheses were proposed using secondary data from Kazakhstan, Kyrgyzstan, Mongolia, Tajikistan, Turkmenistan, and Uzbekistan from 1994… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 102 publications
1
5
0
1
Order By: Relevance
“…Thus, the implication is that foreign borrowing prioritisation for factors that can promote environmental sustainability is lacking. This outcome supports findings by Akam et al (2021), Sadiq et al (2022), Batmunkh et al (2022) and Farooq et al (2023) for HIPCs, BRICS countries, Central Asia countries, and OIC countries, respectively, that debt stock deteriorates ecological sustainability. In contrast, the result opposed the findings in Sadiq et al (2022), Friday (2022), andZeraibi et al (2023) for BRICS countries, Turkey, and emerging economies, respectively.…”
Section: Discussion Of Findingssupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, the implication is that foreign borrowing prioritisation for factors that can promote environmental sustainability is lacking. This outcome supports findings by Akam et al (2021), Sadiq et al (2022), Batmunkh et al (2022) and Farooq et al (2023) for HIPCs, BRICS countries, Central Asia countries, and OIC countries, respectively, that debt stock deteriorates ecological sustainability. In contrast, the result opposed the findings in Sadiq et al (2022), Friday (2022), andZeraibi et al (2023) for BRICS countries, Turkey, and emerging economies, respectively.…”
Section: Discussion Of Findingssupporting
confidence: 86%
“…Sadiq et al (2022) demonstrated using CS-ARDL, AMG, and CCEMG that foreign debt depreciated CO2 emissions in BRICS countries. Also, Batmunkh et al (2022) revealed with the aid of FE, RE, and pooled effect models that debt stock promotes temperature changes in Central Asian countries. Likewise, Akam et al (2022) used the AMG method and confirmed the CO2-emitting effect of external debt in South Africa and Algeria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A. Batmunkh et al (2022), in the process of investigating economic globalisation and environmental sustainability in Central Asia, confirm the hypothesis that the region is at the stage of an industrial economy and propose a roadmap for expanding interstate relations, including joint reclamation of the lands of Southern Mongolia, which will lead to an increase in the yield from steppe lands.…”
Section: Introductionmentioning
confidence: 57%
“…The expansion of international trade is a critical component of globalisation [23]. Today, EG is used in various ways, including export and import, the ER, and FDI [24]. Another study explores the relationship between EG, AVA, and the ecological footprint in the E7 nations: Brazil, China, India, Indonesia, Mexico, Russia and Turkey.…”
Section: Literature Reviewmentioning
confidence: 99%